2013
DOI: 10.3892/etm.2013.1362
|View full text |Cite
|
Sign up to set email alerts
|

Postconditioning with rosuvastatin reduces myocardial ischemia-reperfusion injury by inhibiting high mobility group box 1 protein expression

Abstract: High mobility group box 1 protein (HMGB1) plays an important role in myocardial ischemia-reperfusion (I/R) injury. Rosuvastatin (RS) preconditioning has been reported to reduce myocardial I/R injury. The aim of this study was to investigate whether postconditioning with RS is able to reduce myocardial I/R injury by inhibiting HMGB1 expression in rats. Anesthetized male rats were subjected to ischemia for 30 min and treated once with RS (10 mg/kg, i.v.) 5 min prior to reperfusion for 4 h. Lactate dehydrogenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…These results indicated that simvastatin may exert a cardioprotective effect by decreasing the myocardial expression of HMGB1, which may be associated with the myocardial ischemia-induced inhibition of ROS. This conclusion was consistent with the results of a recent study ( 27 ).…”
Section: Discussionsupporting
confidence: 94%
“…These results indicated that simvastatin may exert a cardioprotective effect by decreasing the myocardial expression of HMGB1, which may be associated with the myocardial ischemia-induced inhibition of ROS. This conclusion was consistent with the results of a recent study ( 27 ).…”
Section: Discussionsupporting
confidence: 94%
“…HMGB1 can activate inflammatory pathways when released from dying cells ( 14 ). In the heart, pre- and post-conditioning with rosuvastatin has been shown to reduce ischemia/reperfusion myocardial injury through the inhibition of HMGB1 ( 29 , 30 ). Therefore, the present study aimed to investigate the effects of rosuvastatin in ADR-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kim et al ( 35 ) showed that rosuvastatin prevented the long-term detrimental effects of ADR on left ventricular function. Ke et al ( 30 ) and Du et al ( 29 ) showed that pre- and post-conditioning with rosuvastatin reduces ischemia/reperfusion myocardial injury through the inhibition of HMGB1. However, the direct effects of rosuvastatin on cardiac function were not observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with HMGB1-neutralizing antibody remarkably ameliorates hepatic, kidney, and brain infarction (Levy et al, 2007; Liu et al, 2007c; Muhammad et al, 2008; Tsung et al, 2005; Watanabe et al, 2005; Wu et al, 2007). Like ischemic preconditioning, pretreatment of mice with HMGB1 can decrease I/R injury (Du et al, 2014; Izuishi et al, 2006; Wu et al, 2013b) and promote tissue regeneration (Biscetti et al, 2011). The protection observed in mice pretreated with HMGB1 partly depends on expression of IL-1R-associated kinase-M, a negative regulator of TLR4 signaling (Izuishi et al, 2006).…”
Section: Hmgb1 and Diseasementioning
confidence: 99%